Respuesta :
◆ QUADRATIC EQUATIONS ◆
[tex] given \: equation \: is \: , \\ \\ {x}^{2} - 5x - 24 = 0 \: \\ \\ = {x}^{2} - 8x + 3x - 24 = 0 \\ \\ = x(x - 8) + 3(x - 8) = 0 \\ \\ = (x + 3)(x - 8) = 0 \: \: (factored \: form) \\ \\ futher \: , \: if \: we \: solve \: for \: x \: , \: \\ \\ we \: get ,\\ \\ \: x = - 3 \\ or \\ x = 8[/tex]
[tex] given \: equation \: is \: , \\ \\ {x}^{2} - 5x - 24 = 0 \: \\ \\ = {x}^{2} - 8x + 3x - 24 = 0 \\ \\ = x(x - 8) + 3(x - 8) = 0 \\ \\ = (x + 3)(x - 8) = 0 \: \: (factored \: form) \\ \\ futher \: , \: if \: we \: solve \: for \: x \: , \: \\ \\ we \: get ,\\ \\ \: x = - 3 \\ or \\ x = 8[/tex]